Barriers for multiparous women to using long-term contraceptive methods in Southeast Asia: case study in Philippines and Indonesia - Agung Dwi Laksono; Nikmatur Rohmah; Hario Megatsari (BMC, 2022)
Abstract Background Multiparous women are supposed to be able to end their reproductive cycle to decrease population growth. This study aimed to analyze barriers for multiparous women to use long-term contraceptive methods (LTCM) in the Philippines and Indonesia. Methods The study population was women aged 15-49 years old who have given birth to a live baby > 1 in the Philippines and Indonesia. The weighted sample size was 12,085 Philippines women and 25,543 Indonesian women. To identify variables associated with the use of LTCM, we analyzed place of residence, age group, education level, marital status, employment status, and wealth status. The final step employed multinomial logistic regression. Results In both countries, the results showed that variables associated with non-user LTCM were younger women, living in rural areas with poor education. Women without partner and unemployed had higher probability to not use LTCM. Finally, low wealth status had a higher probability than the richest multiparous to not use LTCM. Conclusion The study concluded that there were six barriers for multiparous women to use LTCM in the Philippines and Indonesia. The six obstacles were living in rural areas, being younger, poor education, single, unemployed, and low wealth.